2019
DOI: 10.1371/journal.pone.0219829
|View full text |Cite
|
Sign up to set email alerts
|

Empowering therapeutic antibodies with IFN-α for cancer immunotherapy

Abstract: Type 1 IFNs stimulate secretion of IP-10 (CXCL10) which is a critical chemokine to recruit effector T cells to the tumor microenvironment and IP-10 knockout mice exhibit a phenotype with compromised effector T cell generation and trafficking. Type 1 IFNs also induce MHC class 1 upregulation on tumor cells which can enhance anti-tumor CD8 T cell effector response in the tumor microenvironment. Although type 1 IFNs show great promise in potentiating anti-tumor immune response, systemic delivery of type 1 IFNs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…IP-10 is a key chemokine recruiting effector T cells to the tumor microenvironment. Type I IFNs can not only further promote the secretion of IP-10 but also upregulate the expression of MHCⅠ on tumor cells, thus enhancing the antitumor CD8 + T cell effector response ( Najbauer et al, 2019 ). Therefore, TLR4 receptor agonists with the ability to activate both MyD88-dependent and -independent pathways are also promising drugs for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…IP-10 is a key chemokine recruiting effector T cells to the tumor microenvironment. Type I IFNs can not only further promote the secretion of IP-10 but also upregulate the expression of MHCⅠ on tumor cells, thus enhancing the antitumor CD8 + T cell effector response ( Najbauer et al, 2019 ). Therefore, TLR4 receptor agonists with the ability to activate both MyD88-dependent and -independent pathways are also promising drugs for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, for example, we show that apigenin suppressed the TNFα mediated rise in a potent tumor suppressor: CXCL10. While previous studies consistently that CXCL10 is up-regulated in normal vs. tumor tissue (76,77) this particular protein acts as the major tumor suppressor, evoked by IFN-γ treatment and somehow plays a role in the re-expression of MHC-1, PD-L1, the infiltration of anti-tumoral CD4(+) and CD8(+) T cells (78,79), NK cells, cytotoxic lymphocytes (CTLs) to the tumor to turn on immune surveillance and heighted survival odds in diverse human cancers (80)(81)(82). While the beneficial effects of apigenin in cancer are consistently reported, any compound that would turn off the CXCL9, -10, -11/CXCR3 axis could harm the host immunes system to destroy self-malignant tumor tissue (83).…”
Section: Discussionmentioning
confidence: 89%
“…47,48 Additionally, both type I IFN (IFN-α and IFN-β) and type II IFN have been reported to enhance the efficacy of anti-PD1 or anti-PD-L1 in various cancer types, such as melanoma and pancreatic cancer. [13][14][15][16][17] Secondly, various IFN stimulating strategies based on targeting PRRs have been developed to treat cancer, and accumulating evidence indicate that PRR agonists synergize with other therapy approaches and attribute to a better therapeutic efficacy. Deng et al found that the administration of STING agonist (2ʹ3' cGAMP, 10μg) synergized with radiation (20 Gy) and significantly boost anti-cancer immune response in murine colon cancer bearing mouse models.…”
Section: The Implication Of Ifns In Cancer Therapymentioning
confidence: 99%
“…[10][11][12] Moreover, IFNs enhance the therapeutic sensitivity of ICBs in various cancer types. [13][14][15][16][17] These studies suggest that IFN signaling plays an important role in cancer immunotherapy. In this review, we focus on IFNs and cancer immunity, and elaborate on the roles of IFNs in regulating the cancer-immunity cycle.…”
Section: Introductionmentioning
confidence: 99%